Pengembangan Handout Evolusi Berbasis Hasil Penelitian Profil DNA Fingerprinting - Kartika Sari, Nila; Iza, Nikmatul (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
The purpose of this study was to develop a handout based on the results of a DNA Fingerprinting Profile in Javanese-Arabic Ethnics in Malang, East Java, Indonesia for the course of Evolution. Development (Handout) was carried out based on the 4D development model of Thiagarajan. The 4D model has 4 stages, namely define, design, develop, and disseminate, while the research to be carried out is only limited to the develop stage. The research subjects were students of the Biology Education Study Program IKIP Budi Utomo Malang who had taken as many as 40 evolutionary subjects. Data analysis techniques used to analyze quantitative data in the form of validation scores from two material experts, two media experts and readability tests. The instruments used to collect data in the study included validation sheets and questionnaires. The results of the material expert validation analysis included aspects of the completeness of the material, material, questions about evaluation and aspects of material development. The results of expert media validation analysis include aspects of Handout size, Cover Design Handout, Cover Handout Typography, Cover Handout Illustration aspects, Handout Content Design, Typography of Handout Content, Handout Illustration, Language Feasibility, and Presentation Completeness. The results of the readability test analysis include aspects of the material ease, the victory of the handout of understanding material, and renewal of material. Based on the results of the analysis data in this development research, it can be concluded that the average results of the assessment from the material expert validator was obtained with a percentage of 89.85% with the category Very Valid. The average assessment results from media expert validators with a percentage of 98.22% with the category Very Valid. The average assessment results from the readability test with a percentage of 92.73% with the category Very Valid.